2021
DOI: 10.1021/acsomega.1c01520
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Nitrogen Doping of Nanocrystalline Graphene Films with Tunable Pyridinic-N and Pyrrolic-N by Cold-Wall Plasma-Assisted Chemical Vapor Deposition

Abstract: We report a viable method to produce nanocrystalline graphene films on polycrystalline nickel (Ni) with enhanced N doping at low temperatures by a cold-wall plasma-assisted chemical vapor deposition (CVD) method. The growth of nanocrystalline graphene films was carried out in a benzene/ammonia/argon (C6H6/NH3/Ar) system, in which the temperature of the substrate heated by Joule heating can be further lowered to 100 °C to achieve a low sheet resistance of 3.3 kΩ sq–1 at a high optical transmittance of 97.2%. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…The growth conditions of CVD were often harsh because the growth process required high-temperature cleavage of carbon precursors followed by rapid cooling to form graphene. In recent years, many scholars had conducted a lot of researches on these growth factors, and the CVD growth parameters of graphene had been optimized continuously, and now there are some feasible methods to synthesize high-quality graphene films at low temperature, [60] low pressure, [61] and metal-free substrates, [62] which gradually got rid of the constraints of strict growth conditions and expanded the applicability of CVD methods. After the research of our group, we found that the defects of graphene were directly influenced by the growth conditions, and in plasma enhanced chemical vapor deposition (PECVD), the defect type of graphene changed from vacancy to boundary type with the increase of ion source power; the morphology of graphene changed from 2D to 3D with the increase of temperature or ion source power, [63] which was beneficial for us to prepare especial graphene on non-catalytic substrate, such as sapphire, GaN, and AlN substrates.…”
Section: Cvd Methodsmentioning
confidence: 99%
“…The growth conditions of CVD were often harsh because the growth process required high-temperature cleavage of carbon precursors followed by rapid cooling to form graphene. In recent years, many scholars had conducted a lot of researches on these growth factors, and the CVD growth parameters of graphene had been optimized continuously, and now there are some feasible methods to synthesize high-quality graphene films at low temperature, [60] low pressure, [61] and metal-free substrates, [62] which gradually got rid of the constraints of strict growth conditions and expanded the applicability of CVD methods. After the research of our group, we found that the defects of graphene were directly influenced by the growth conditions, and in plasma enhanced chemical vapor deposition (PECVD), the defect type of graphene changed from vacancy to boundary type with the increase of ion source power; the morphology of graphene changed from 2D to 3D with the increase of temperature or ion source power, [63] which was beneficial for us to prepare especial graphene on non-catalytic substrate, such as sapphire, GaN, and AlN substrates.…”
Section: Cvd Methodsmentioning
confidence: 99%
“…This method of production is very costefficient for the bulk synthesis of CNTs. Juggernauth et al [95] used the CVD process and adopted step-wise control of various process variables such as gas flow, pressure, and time for the growth of films. This allowed them to successfully deposit the vanadium ox- Although the basic principle of the CVD process remains the same, a lot of research modification has been done over the past few years to cater to different kinds of NC materials.…”
Section: Chemical Vapor Depositionmentioning
confidence: 99%
“…The process parameters to produce these CNT-mediated vanadium oxide structures could easily be altered for a variety of functional applications such as electrochemical cells, physical and chemical sensors, etc. Ariffin et al [95] also reported a novel method. They used a cold-wall plasma-assisted CVD process to synthesize nitrogen-doped NC graphene layers on a polycrystalline Ni substrate at considerably lower temperatures of around 100 • C. This process could be used to develop transparent nano-scale devices soon.…”
Section: Chemical Vapor Depositionmentioning
confidence: 99%
“…For high-performance semitransparent solar cells, a method to improve the conductivity while maintaining excellent T of Gr is required. Chemical doping is one of the techniques to reduce the sheet resistance ( R s ) of Gr simply, but the R s of Gr increases over time due to deterioration in air. Therefore, it is very important to find a dopant that can maintain the R s of Gr for a long time at room temperature.…”
Section: Introductionmentioning
confidence: 99%